Ocean Acidification as Physical Indicator for Climate Change - Ba Naga, Mohammed Hussein (Maritime Park: Journal of Maritime Technology and Society, 2022)
Atmospheric carbon dioxide concentration is expected to exceed 500 parts per million and global temperatures to rise by at least 2°C by 2050 to 2100, values that significantly exceed those of at least the past 420,000 years during which most extant marine organisms evolved. Under conditions expected in the 21st century, global warming and ocean acidification will be a greatly concerned.